Youth and future. Educational-labor projects, horizons and temporalities in young people from La Plata, Argentina (Praxis Educativa, 2022)
This article proposes to analyze the post-graduation projects in terms of work and education of young students to inquire how they are shown, in the imagined futures, readings from reality, of the possible and the desirable crossed by diverse experiences of inequality. For our objective, we used an empirical corpus formed by 155 surveys and 37 in-depth interviews with students between the ages of 18 and 24 who were in the last year of their secondary education in 2019 in two public institutions in the city of La Plata. From these materials we identify and characterize three post-graduate projects: work, continue higher education and combine both activities. The analysis allowed us to identify differences in terms of the projects, the horizons and the temporalities intertwined in them that account how the symbolic dimensions of inequality take part in the future anticipations of these young people.
Keywords: youth; high school; future; social inequality; labor insertion